Identification of Highly Potent α‐Glucosidase Inhibitors from Artocarpus integer and Molecular Docking Studies. Issue 12 (11th November 2021) - Duong, Thuc‐Huy; Nguyen, Huy Troung; Nguyen, Chuong Hoang; Tran, Nguyen‐Minh‐An; Danova, Ade; Tran, Thi‐Minh‐Dinh; Vu‐Huynh, Kim Long; Musa, Vassana; Jutakanoke, Rumpa; Nguyen, Ngoc‐Hong; Sichaem, Jirapast
Abstract: A new natural Diels‐Alder adduct (3 ) was isolated from the leaves and stem bark of Artocarpus integer, along with seventeen known compounds (1, 2, and 4 –18 ). Structural elucidation was conducted using NMR and HR‐ESI‐MS data, and comparisons were made with previous studies. Deoxyartonin I (3 ) exhibited the most potent α ‐glucosidase inhibition (IC50 7.80±0.1 μM), outperforming the acarbose positive control. This was mixed‐mode inhibition, as indicated by the intersect in the second quadrant of each respective plot. An in silico molecular docking model and the pharmacokinetic features of 3 suggest that it is a potential inhibitor of enzyme α ‐glucosidase, and is therefore a lead candidate as a drug against diabetes mellitus. Abstract :